- #1

medeski

- 1

- 0

## Homework Statement

Prove by induction that gamma(v+1)(v+1)(v+2)...(v+k)=gamma(v+k+1) for k=1,2,3...

## Homework Equations

Really just using the relation x*gamma(x)=gamma(x+1)

## The Attempt at a Solution

for a basis gamma(v+1)(v+1)=gamma(v+1+1)

so holds for k = 1

inductive hypothesis

gamma(v+1)(v+n)=gamma(v+n+1)

now for k = n+1 i get

gamma(v+1)(v+n+1)=gamma(v+n+2)

but what confuses me is if i use the above relationship, then gamma(v+n+2) should equal (v+n+1)*gamma(v+n+1), unfortunately my proof claims it's equal to gamma(v+1)(v+n+1). I'm lost at this step